2019
DOI: 10.1101/744466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell molecular and cellular architecture of the mouse neurohypophysis

Abstract: AcknowledgementsWe thank Yael Kuperman for her help in neurohypophysis dissection; Hagit Dafni for providing C57BL6 mice for dissociation protocol optimization; Stefan Jung for providing he Cx3cr1:GFP mice and Shalev Itzkovitz for the smFISH probes; Amrutha Swaminathan and Ludmila Gordon for their valuable comments on the text and figures and Hanjie Li for his advices on cluster annotation. Abstract:The neurohypophysis (NH), located at the posterior lobe of the pituitary, is a major neuroendocrine tissue, whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 56 publications
(87 reference statements)
4
23
0
Order By: Relevance
“…( D ) Histogram showing over-representation analyses (ORA) comparing zebrafish pituicyte to scRNA-Seq gene sets of adult mouse neurointermediate pituitary lobe (Chen Q et al, 2020) or human fetus pituitary (Zhang et al, 2020). The bar lengths indicate -log 10 (FDR), and the color-coded scale bars depict the number of overlapping genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…( D ) Histogram showing over-representation analyses (ORA) comparing zebrafish pituicyte to scRNA-Seq gene sets of adult mouse neurointermediate pituitary lobe (Chen Q et al, 2020) or human fetus pituitary (Zhang et al, 2020). The bar lengths indicate -log 10 (FDR), and the color-coded scale bars depict the number of overlapping genes.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that commonly used marker genes, which have been so far considered as ‘pituicyte-specific’ display promiscuous cell-type specificity (Chen Q et al, 2020). This highlighted the need for a better molecular and cellular characterization, as well as an improved markers definition of pituitary cells and in particular the pituicytes, ideally leading to the generation of new transgenic tools in rodents and zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports analysing single cells RNA sequencing (scR-NAseq) of rodent anterior pituitary cells utilising unbiased clustering methods have variably described FS and Sox2+ve cells as single or multiple cell types. [54][55][56][57] It is important to note that differences in pituitary dissection, with the inclusion of the intermediate and posterior pituitary that contains cell types such as pituicytes and epithelial-like cells expressing markers associated with FS cells, 58 may affect the identification of potential subpopulations. Indeed, this recent description of the expression in pituicytes and epitheliallike cells of markers used in previous analyses of FS cell function may require the reinterpretation of some older studies, in particular those using dispersed pituitary cells.…”
Section: Heterogeneitymentioning
confidence: 99%